Characterization of 17-Cyclopropylmethyl-3,14β-dihydroxy-4,5α-epoxy-6α-(indole-7-carboxamido)morphinan (NAN) as a Novel Opioid Receptor Modulator for Opioid Use Disorder Treatment - Obeng, Samuel (ACS Chem Neurosci, 2019)
The opioid crisis is a significant public health issue with more than 115 people dying from opioid overdose per day in the United States. The aim of the present study was to characterize the in vitro and in vivo pharmacological effects of 17-cyclopropylmethyl-3,14β-dihydroxy-4,5α-epoxy-6α-(indole-7-carboxamido)morphinan (NAN), a μ opioid receptor (MOR) ligand that may be a potential candidate for opioid use disorder treatment that produces less withdrawal signs than naltrexone. The efficacy of NAN was compared to varying efficacy ligands at the MOR, and determined at the δ opioid receptor (DOR) and κ opioid receptor (KOR). NAN was identified as a low efficacy partial agonist for G-protein activation at the MOR and DOR, but had relatively high efficacy at the KOR. In contrast to high efficacy MOR agonists, NAN did not induce MOR internalization, downregulation, or desensitization, but it antagonized agonist-induced MOR internalization and stimulation of intracellular Ca(2+) release. Opioid withdrawal studies conducted using morphine-pelleted mice demonstrated that NAN precipitated significantly less withdrawal signs than naltrexone at similar doses. Furthermore, NAN failed to produce fentanyl-like discriminative stimulus effects in rats up to doses that produced dose- and time-dependent antagonism of fentanyl. Overall, these results provide converging lines of evidence that NAN functions mainly as a MOR antagonist and support further consideration of NAN as a candidate medication for opioid use disorder treatment.